Regional Stiffness and Hardening Indices: New Indicators Derived from Multidimensional Dynamic CTA for Aneurysm Risk Assessment - Tianming Huang; Xiaoyu Qi; Lan Cao; Ming Yang; Huan Luo; Qin Li; Peidong Qian; Jia Lu; Ziqiao Lei; Yuanming Luo; Chao Yang (Advanced Science)
Abstract Two indices, indicating the regional average stiffness and the pace of strain hardening respectively, are derived from the nonlinear stress–strain behavior obtained from biomechanical analysis of aneurysm. A comprehensive method based on electrocardiographic‐gated multidimensional dynamic computed tomography angiography (MD CTA) is developed for extracting these mechanical characteristics in vivo. The proposed indices are evaluated by 26 cases including 9 healthy, one aortosclerosis, and 16 abdominal aortic aneurysm cases. The difference of SSI and dSSI value between aneurysmal and healthy groups is up to orders in magnitude. Significant correlation of these indices with the clinical indicator of aneurysm diameter is found. Logistic models based on these indices are capable to sharply discriminate the healthy and the aneurysmal arteries with AUC>0.98. This work introduces new tools and new indices for aortic mechanical assessment which may shed light on understanding the mechanical condition, pathological state and eventually benefit clinical decision‐making.